Vol. 3, No. 1, September 2021 - Nur Hidayat (Scientia Regendi, 2021)
The use of Posyandu services in Indonesia from year to year has decreased by both boys and girls in the span of years and the quality of Posyandu services has also decreased with an indication of a 14% decrease in the coverage of growth monitoring from 2008 and the low ownership of KMS to a decrease of 24% in 2008. At the same time, this cannot be separated from the role of cadres, posyandu components that have a role and at the same time a driving force in providing health services, namely posyandu cadres. This condition shows that the existence of posyandu cadres requires maximum empowerment so that the presence and activity of cadres will certainly greatly affect the quality of posyandu services in each region. This shows the influence of the presence and activity of cadres on the quality of posyandu health services. The purpose of this study was to determine the effect of cadre behavior consisting of knowledge, attitudes and practices of posyandu cadres on maternal service satisfaction for infants in Posyandu, Ciamis District, the population was 533 cadres with a total sample of 59 cadres. With quantitative and cross-sectional methods. The results of this study indicate that the knowledge, attitudes and practices of posyandu cadres in the Ciamis sub-district are in sufficient category which is associated with satisfaction with posyandu services for mothers of children under five and the correlation results between research variables have a relationship or influence between knowledge, attitudes and practices of cadres on service satisfaction. Integrated Healthcare Center